Platelets express steroidogenic 17β–hydroxysteroid dehydrogenases - Gnatenko, Dmitri V.; Cupit, Lisa D.; Huang, Emily C.; Dhundale, Anilkumar; Peter, L. Perrotta; Bahou, Wadie F. (Thrombosis and Haemostasis, 2005)
Human blood platelets have important, regulatory functions in diverse hemostatic and pathological disorders, including vascular remodeling, inflammation, and wound repair. Microarray analysis was used to study the molecular basis of essential thrombocythemia, a myeloproliferative disorder with quantitative and qualitative platelet defects associated with cardiovascular and thrombohemorrhagic symptoms, not infrequently neurological. A platelet-expressed gene (HSD17B3) encoding type 3 17β-hydroxysteroid dehydrogenase (previously characterized as a testis-specific enzyme catalyzing the final step in gonadal synthesis of testosterone) was selectively down-regulated in ET platelets, with reciprocal induction of the type 12 enzyme (HSD17B12). Functional 17β-HSD3 activity corresponding to ∼10% of that found in murine testis was demonstrated in normal platelets. The induction of HSD17B12 in ET platelets was unassociated with a concomitant increase in androgen biosynthesis, suggesting distinct functions and/or substrate specificities of the types 3 and 12 enzymes. Application of a molecular assay distinguished ET from normal platelets in 20 consecutive patients (p < 0.0001). These data provide the first evidence that distinct subtypes of steroidogenic 17β−HSDs are functionally present in human blood platelets, and that the expression patterns of HSD17B3 and HSD17B12 are associated with an uncommon platelet disorder manifest by quantitative and qualitative platelet defects.
Keywords: Platelets; hydroxysteroid dehydrogenases; microarray; essential thrombocythemia